COMPARISON OF VILLAGE DEVELOPMENT BEFORE AND AFTER VILLAGE FUND IMPLEMENTATION IN NAGAN RAYA DISTRICT - arroyyan ramly (IAIN Langsa, 2021)
This study aims to analyze and see the effectiveness of the distribution of the use of village funds in Kuala Subdistrict, Nagan Raya Regency and its relationship with poverty levels. The data used is in the form of time series data from 2015 to 2018 which is collected through primary and secondary data. Primary data were obtained by directly visiting villages in the Kuala sub-district. Meanwhile, secondary data were obtained from the website of the Central Statistics Agency (BPS), document review, articles related to the object of research. This study conducted observations of 10 villages as a sample of 17 villages in Kuala District. The analysis method uses panel data regression with the random effect model (REM) analysis method. From the regression results of the random effect model, it was found that the village fund variable had a positive and significant effect on poverty with a probability of 0.0000 = p-value α = 5%. Then the village fund allocation variable has a significant negative effect on poverty with a probability of 0.0000 = p-value α = 5%. This means that adding 1% of village funds or increasing village funds will reduce poverty in Kuala Subdistrict, Nagan Raya Regency.